Evaluation of vascular endothelial growth factor level in tear and serum among diabetic patients - Jeat, Ang Wen (2018)
Introduction Vascular endothelial growth factor (VEGF) has been postulated to play a role in the pathogenesis and progression of diabetic retinopathy (DR). Thus, detection of VEGF level in ocular tissue may perhaps provide insight into a role of VEGF in pathogenesis of DR. Objective: The objective of this study was to evaluate the VEGF in serum and tears between different type of DR severity among type 2 diabetes mellitus (DM) patients and to determine the correlation between serum and tears VEGF levels. Methods: A comparative cross-sectional study was conducted at a tertiary hospital in Malaysia, Hospital Universiti Sains Malaysia (USM) between August 2016 and May 2018 involving type 2 DM patients with different status of DR [no DR, non-proliferative DR (NPDR), proliferative DR (PDR)]. Tear samples were collected using no.41 Whatman filter paper (Schirmer’s strips) and 5 mls of blood sample were drawn by venous puncture. VEGF levels in tears and serum were measured by enzyme-linked immunosorbent assay. ixResults: A total of 88 type 2 DM patients (no DR: 30 patients, NPDR: 28 patients, PDR: 30 patients) were included into the study. Mean tear VEGF were significantly higher in NPDR and PDR groups (114.9 SD 8.6 pg/mL and 149.5 SD 10.4 pg/mL respectively) as compared to no DR (41.2 SD 11.3 pg/mL, p < 0.001). There was no significant difference of mean serum VEGF between the three groups. There was a fair correlation between serum and tears VEGF (p = 0.015, r = 0.263). Conclusion: Among type 2 DM patients, VEGF levels in tears were higher amongst patients with DR compared to those without DR. Tear VEGF levels were also significantly associated to the severity of DR. There was a fair correlation between serum and tears VEGF. Detection of VEGF in tears is a good non-invasive predictor test for severity of DR. A large cohort study is needed for further evaluation.